Sacred words and worlds: geography, religion, and scholarship, 1550 - 1700 - Šālew, Ṣûr (History of science and medicine library, 2012)
Early modern Geographia Sacra: Themes and approaches -- The Antwerp polyglot Bible: Maps, scholarship, and exegesis -- Antiquarian zeal and sacred measurement on the road to Jerusalem -- The Phoenicians are coming! Samuel Bochart's Protestant geography -- Putting the Church on the map: Ecclesiastical cartography across the denominational divide -- Epilogue -- Appendix: Extant manuscripts of Samuel Bochart